Behavioral Finance Meets Experimental Macroeconomics: On the Determinants of Currency Trade Decisions - Kaiser, Johannes; Kube, Sebastian (The journal of behavioral finance, 2009)
A novel approach which conjoins elements of experimental macroeconomics and behavioral finance allows us to study the components of industrial firms' currency trade decisions in the controlled environment of a laboratory. We analyze how firms operate in the currency market in a deterministic two-country model with two currencies. Consistent with presumptions of real-world behavior, subjects in our experiment tend to base their trade decisions on definite rather than on uncertain key data: Interest rates have a high impact, while technical analysis plays a minor role. We finally demonstrate how a simple decision rule that incorporates our findings might outperform the actually observed trade decisions.